The Effect of 12-Month Green Tea Extract Supplementation and Impact of Catechol-O-Methyltransferase Genotype on Blood Pressure in Women Who Are Post-menopause. (7th June 2021) - Acosta, Laura; Radler, Diane Rigassio; Kurzer, Mindy; Samavat, Hamed
Abstract: Objectives: Green tea extract (GTE) is thought to have antihypertensive properties, potentially mediated by epigallocatechin gallate (EGCG). The objective of this study was to evaluate the effect of GTE supplementation on blood pressure (BP) among postmenopausal women with elevated BP or hypertension (HTN). Methods: This study was a secondary analysis of the Minnesota Green Tea Trial (MGTT), a randomized, placebo-controlled, double-blinded trial in which healthy, postmenopausal women were randomized to consume GTE (two capsules each morning and evening with meals, 843 mg/day of EGCG) or placebo, daily for 12 months. MGTT subjects who had elevated BP or HTN at baseline (N = 495) were included. Primary outcomes were changes in systolic (SBP) and diastolic (DBP) blood pressure. Chi-square, Fisher's exact, Independent samples t-test, and ANCOVA adjusting for baseline BP and weight changes, were conducted to evaluate frequency distributions and between-group differences. Findings were stratified by age, BMI, use of antihypertensive medication, BP status, and catechol-O-methyltransferase ( COMT ) genotype. Results: Ninety-seven % of subjects were white and non-Hispanic. The sample had a mean age of 61.0 years and mean BMI of 25.9 kg/m 2 at baseline. There were no significant differences in SBP or DBP changes between treatment groups in the total sample, or between COMT genotypes (low-activity versus high-activity) within the GTE group. However, there were significant interactions between treatment group and baseline BMI ( P = 0.02), and baseline age ( P = 0.03). Significant reductions in mean SBP in response to GTE were observed in subjects with BMI of 18.5–24.9 kg/m 2 (−6.7 mmHg, P = 0.005), and subjects aged 61–70 years (−6.0 mmHg, P = 0.004), compared to subjects with BMI ≥ 25.0 kg/m 2 and those aged 50–60 years. There were no significant interactions between treatment group and baseline BP status or baseline use of antihypertensive medication. Conclusions: GTE may reduce SBP in postmenopausal women aged 61–70 years and those with normal weight status. Questions for future research may include the optimal dosage and duration of GTE supplementation, and the relative bioavailability and effectiveness of GTE capsules versus green tea beverages. Funding Sources: NIH/National Cancer Institute.